2021
DOI: 10.1177/10711007211003565
|View full text |Cite
|
Sign up to set email alerts
|

Open vs Minimally Invasive Scarf Osteotomy for Hallux Valgus Correction: A Randomized Controlled Trial

Abstract: Background: Minimally invasive (MI) surgery is becoming increasingly popular in the treatment of hallux valgus (HV). The scarf osteotomy is an effective procedure with a track record in open HV surgery. We adapted this effective osteotomy to MI surgery as a novel technique never reported before. The aim of this study was to compare the clinical and radiologic outcomes of patients who underwent open or MI scarf. Methods: Between 2017 and 2018, 58 patients were randomized to either open or MI scarf to treat HV d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Follow-up times were highly variable, ranging from 6 months to 7 years. Among the included studies, 8 studies ( 15 , 17 , 24 , 26 , 28 , 29 , 31 , 35 ) were RCTs, 2 studies ( 4 , 14 ) were prospective comparative studies, and 12 studies ( 5 , 13 , 16 , 18 , 22 , 23 , 25 , 27 , 30 , 32 34 ) were retrospective comparative studies. A total of 10 studies ( 13 , 17 , 22 28 , 32 ) reported on the 2G percutaneous hallux valgus surgery, in which 7 studies ( 13 , 22 25 , 28 ) involved Bösch osteotomy and 3 studies ( 17 , 26 , 27 ) involved a simple, an effective, a rapid, and an inexpensive (SERI) technique.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Follow-up times were highly variable, ranging from 6 months to 7 years. Among the included studies, 8 studies ( 15 , 17 , 24 , 26 , 28 , 29 , 31 , 35 ) were RCTs, 2 studies ( 4 , 14 ) were prospective comparative studies, and 12 studies ( 5 , 13 , 16 , 18 , 22 , 23 , 25 , 27 , 30 , 32 34 ) were retrospective comparative studies. A total of 10 studies ( 13 , 17 , 22 28 , 32 ) reported on the 2G percutaneous hallux valgus surgery, in which 7 studies ( 13 , 22 25 , 28 ) involved Bösch osteotomy and 3 studies ( 17 , 26 , 27 ) involved a simple, an effective, a rapid, and an inexpensive (SERI) technique.…”
Section: Resultsmentioning
confidence: 99%
“…Tay et al ( 34 ) performed a retrospective study to compare between the MICA and scarf/akin surgery. Two studies ( 4 , 31 ) performed a comparison of the mini-scarf with open scarf osteotomy. Guo et al ( 33 ) conducted a retrospective comparative study for a comparison of percutaneous oblique osteotomy (POO) with open chevron osteotomy.…”
Section: Resultsmentioning
confidence: 99%
“…Surgery duration and the time using fluoroscopy was not measured in the present study; nevertheless, the amount of radiation and surgical time decrease while surgeon experience increases. 33 Tay et al 32 reported significant improvements in VAS score 1 week after surgery with third-generation MIS, and these results could explain the differences between the first, second, and third generations of MIS. Similar results were reported by Neufeld et al 24 with MICA.…”
Section: Discussionmentioning
confidence: 95%
“…Tay et al 32 reported similar results comparing MICA with scarf + Akin at 6 and 24 months, although the preoperative HVA values were smaller than those in the present study. 14,21,32 Torrent et al 33 compared open to MIS scarf osteotomy with similar clinical and radiographic results between both techniques. The MIS technique was faster than open although with more fluoroscopic radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation